Effective strategic education for the youth in Muslim cultures - Jelyani, Mohsen Zareie (2010)
Today, education serves as a core part of social development. The earlier history of Islamic education is actually a landmark of expanding commitment to education, both formal and informal. The decolonization of education or what we refer to as long life education, has transformed and broadened the corresponding initiatives into an intl humanitarian efforts that reaches out to hundreds of Muslim communities in developing countries. To respond properly to such needs, we need to invest in a wide array of educational institutions, at all levels. In doing so, we can also help to bridge the rift between the western type of education and the Muslim counterpart. However, such fundamental diversity and pluralism may give rise to certain cultural, legal and even historical issues. This paper is going to touch on such issues in details and propose strategies to overcome the related challenges.